Cleaved high molecular weight kininogen accelerates the onset of endothelial progenitor cell senescence by induction of reactive oxygen species - Dai, Jihong (2011)
OBJECTIVE: Cleaved high molecular weight kininogen (HKa), an activation product of the plasma kallikrein-kinin system, inhibits endothelial cell functions. We questioned whether HKa affects the function of endothelial progenitor cells (EPCs) and accelerates their senescence. METHODS AND RESULTS: Treatment with HKa for two weeks markedly inhibited the formation of large colonies and proliferation of EPCs on collagen surfaces, whereas HKa did not affect collagen-mediated EPC adhesion and survival. Concomitantly, treated EPCs displayed flattened and giant cell morphological changes with formation of intracellular vacuoles. As determined by acidic β-galactosidase staining, HKa increased senescent EPCs by 2 fold and >3 fold after culture for one and two weeks, respectively. Additionally, HKa suppressed the telomerase activity of EPCs. HKa concentration-dependently increased the generation of intracellular reactive oxygen species (ROS), and markedly upregulated p38 kinase phosphorylation and prosenescence molecule p16(INK4a) expression. SB203580, a p38 inhibitor attenuated the level of HKa-enhanced p16(INK4a) expression. Either quenching of ROS or inhibition of p38 kinase prevented HKa-induced EPC senescence. CONCLUSION: HKa accelerates the onset of EPC senescence by activating the ROS - p38 kinase - p16(INK4a) signaling cascade. This novel activity of HKa points out the likelihood for HKa serving as an endogenous inducer of EPC senescence.